Heat-induced transformation of nickel-coated polycrystalline diamond film studied in situ by XPS and NEXAFS - Sedelnikova, Olga V.; Fedoseeva, Yuliya V.; Gorodetskiy, Dmitriy V.; Palyanov, Yuri N.; Shlyakhova, Elena V.; Maksimovskiy, Eugene A.; Makarova, Anna A.; Bulusheva, Lyubov G.; Okotrub, Aleksandr V. (Beilstein Journal of Nanotechnology, 2025)
Controlling high-temperature graphitization of diamond surfaces is important for many applications, which require the formation of thin conductive electrodes on dielectric substrates. Transition metal catalysts can facilitate the graphitization process, which depends on the diamond face orientation. In the present work, the role of a nickel coating on the electronic structure and chemical state of graphite layers formed on the surface of a polycrystalline diamond (PCD) film with mixed grain orientation was studied. A synthetic single-crystal diamond (SCD) with a polished (110) face was examined for comparison. The samples were coated with a thin nickel film deposited by thermal evaporation. The graphitization of diamond with and without a nickel coating as a result of high-vacuum annealing at a temperature of about 1100 °C was studied in situ using synchrotron-based X-ray photoelectron spectroscopy (XPS) and near-edge X-ray absorption fine structure (NEXAFS) methods. XPS data revealed the formation of a thin graphite-like film with low-ordered atomic structure on the surface of the nickel-coated PCD film. The chemical state of sp2-hybridized carbon atoms was found to be insensitive to the face orientation of the diamond micro-sized crystallites; however, the layer defectiveness increased in areas with fine-dispersed crystallites. According to NEXAFS and Raman spectroscopy data, the most ordered atomic structure of graphitic layers was obtained by annealing nickel-coated SCD. The angular dependence of NEXAFS C K-edge spectra of nickel-coated (110) face after annealing discovered the vertical orientation of sp2-hybridized carbon layers relative to the diamond surface. The observed behavior suggests that sp2 carbon layers were formed on the diamond surface due to its saturation by released carbon atoms as a result of etching by nickel.
Keywords: graphitization; near-edge X-ray absorption fine structure spectroscopy; nickel coating; polycrystalline diamond film; single-crystal diamond; X-ray photoelectron spectroscopy